2001
DOI: 10.1211/0022357011776234
|View full text |Cite
|
Sign up to set email alerts
|

Contradistinction between doxorubicin and epirubicin: in-vivo metabolism, pharmacokinetics and toxicodynamics after single- and multiple-dosing in rats

Abstract: There is compelling in-vitro evidence that the evaluation of doxorubicin or epirubicin pharmacokinetics based solely on plasma concentration may not fully elucidate the differences between the two drugs. Both compounds bind to erythrocytes and their different binding to haemoglobin may influence their disposition in the body. The purpose of the present study was to compare the pharmacokinetics and metabolism of doxorubicin and epirubicin based on the plasma concentration, amount associated with blood cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The assay was able to measure plasma doxorubicin concentrations to 20 ng/mL, about 0.5% of the average C MAX seen during the infusion period. It appeared that in the parrot the systemic clearance per kilogram of doxorubicin was similar to that in healthy dogs, 12 but more than twice that in rats, 13 and in human cancer patients. 14,15 This is supported by the relatively shorter elimination (β-phase) half-life and the smaller total volume of distribution per kilogram in the parrot.…”
Section: Discussionmentioning
confidence: 89%
“…The assay was able to measure plasma doxorubicin concentrations to 20 ng/mL, about 0.5% of the average C MAX seen during the infusion period. It appeared that in the parrot the systemic clearance per kilogram of doxorubicin was similar to that in healthy dogs, 12 but more than twice that in rats, 13 and in human cancer patients. 14,15 This is supported by the relatively shorter elimination (β-phase) half-life and the smaller total volume of distribution per kilogram in the parrot.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, this study revealed a great difference between doxorubicin and epirubicin pharmacokinetic constants, with the former having higher serum concentration and AUC and a lower rate of body clearance than the latter. Ramanathan‐Girish and Boroujerdi [30] found a stronger interaction between doxorubicin and blood cells compared with epirubicin and so they detected a higher AUC for multiple doses of doxorubicin compared with epirubicin. The authors suggested that the continual increase in AUC of doxorubicin associated with blood cells may play a significant role in the cardiotoxicity of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%